Welcome to the Dark Side: Use of Humour in Indoctrinating to Extremist Ideologies - Sinokki, Jani (Journal for the theory of social behaviour, 2025)
The paper argues that humour can be very effective in disseminating extremist ideologies, in part because of humour's inherent capacity to hinder critical reflection and in part because humour requires bringing together two conflicting frames of interpretation. With extremist humour, the other frame needed to make sense of what is funny is the extremist ideology itself. Thus, merely grasping what is funny in an extremist joke entails the ability to see and interpret other things through the lenses of that extremist ideology. Although this ability does not amount to accepting the ideology, the ability is the crucial first step in the process of converting audiences to the ideology. I argue that ideology should be understood as an interpretational framework, following the political theorist Michael Freeden, so that it is something that can be parsed from the joke by the audience making sense of the joke. This view of ideology opens a way for understanding how indoctrination to an ideology with humour occurs, explaining how ideology is transmitted, how it bypasses critical reflection and how it might cause dogmatism. The paper argues that this power stems not only from the cognitive mechanisms of humour processing but also from the deeper human needs that humour serves, the desire for communality and belonging and the creation of in‐group/out‐group distinctions (schismogenesis). The neo‐Nazi website, the Daily Stormer, which is notorious for using humour to garner new adherents for the white supremacist ideology and antisemitism, is used as a case study.